A real-world pharmacovigilance analysis of eslicarbazepine acetate using the FDA adverse events reporting system (FAERS) database from 2013 (Q4) to 2024 (Q1) - Tang, Huafei; Xu, Jing; Zhang, Xian; Chen, Chunliang; Song, Ge; Ma, Rui; Zhao, Jinjing; Zhao, Qiang (Frontiers in Pharmacology, 2024)
The principal aim of the present study was to scrutinize eslicarbazepine acetate related AEs by leveraging data from the US Food and Drug Administration Adverse Event Reporting System (FAERS) database. Methods: By extracting all available data since the FDA approval of ESL (2013Q4-2024Q1), disproportionality analysis was performed using reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN) and multi-item gamma Poisson shrinker (MGPS) algorithms. Demographic information, time of onset and gender-specific signal detection were also examined. In addition, a special screening process for designated medical events (DME) was implemented to focus on the evaluation and comparison of safety signals within DME and System Organ Classification (SOC) level, as well as SMQ (Standardised MedDRA Queries) level. Stratified analysis by logistic regression is employed to examine the variations across different gender and age groups. Results: A total of 5,719 AE reports and 1,907 reported cases were obtained. ESL related AEs were identified in relation to 27 SOCs, among which the significant positive SOCs were nervous system disorders , injury poisoning and procedural complications, etel. There were 86 severely disproportional preferred terms that complied with the four algorithms. Most AEs occurred within the first month after treatment. According to the 86 valuable positive signals with DME screening results, 3 signals of dermatitis exfoliative, stevens-johnson syndrome, drug reaction with eosinophilia and systemic symptoms were consistent with PT signals on the DME-list, with the 3 PTs focusing on skin and subcutaneous tissue disorders and hypersensitivity. Males are more commonly affected by seizures than females. Seizures, hyponatremia, and confusional states were more frequently observed in the elderly population, while aggression, irritability, DRESS, and abnormal behavior were found to be more common in the pediatric population. Both the children and elderly groups exhibited a higher proportion of agitation than the adult group. Conclusion: Our research enhances the safety and tolerability profile of ESL, but the clinical use of ESL should be noticed and avoided in relation to AEs since it raises the risk of dermatitis exfoliative, stevens-johnson syndrome. Particular attention should be paid to DRESS in children and hyponatremia in the elderly.